2016
DOI: 10.5606/kbbihtisas.2016.88725
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adenoid hypertrophy and pulmonary function tests in children with mild asthma

Abstract: Consequently, significantly higher values of FEF25-75 in the group that used nasal steroid suggest that adenoid hypertrophy affects the airway obstruction. Moreover, absence of airway obstruction symptoms in patients with mild adenoid hypertrophy suggests pulmonary function tests may help to decide performing adenoidectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…The final forced mid-expiratory flow rate (FEF 25-75) values were statistically higher in patients who were using nasal steroids. 9 In another study by Goldstein et al, few patients demonstrated statistically significant improvement after FESS in asthma symptom scores (1 patient), medication use scores (1 patient), or pulmonary function test results (2 patients), which is in clearly proven to be the case in accordance to our findings as well. 7…”
Section: Discussionsupporting
confidence: 91%
“…The final forced mid-expiratory flow rate (FEF 25-75) values were statistically higher in patients who were using nasal steroids. 9 In another study by Goldstein et al, few patients demonstrated statistically significant improvement after FESS in asthma symptom scores (1 patient), medication use scores (1 patient), or pulmonary function test results (2 patients), which is in clearly proven to be the case in accordance to our findings as well. 7…”
Section: Discussionsupporting
confidence: 91%
“…Adenoidectomy can contribute to an improvement in FEV1 by reducing airway resistance and facilitating smoother airflow. This can result in a greater volume of air expelled from the lungs within the first second of exhalation [1,20,[23][24][25][26]. Our study observed a significant increase in FEV1, pre-op it was 1.26% ± 0.52%, postop averaged 1.636% ± 0.551 (p < 0.001), showing adenoidectomy's impact on one-second forced exhalation.…”
Section: Discussionmentioning
confidence: 60%
“…AH is characterized by the excessive growth of adenoid tissues in the upper airway, leading to varying degrees of airway obstruction. This obstruction can disrupt normal airflow and potentially affect lung function parameters measured by PFTs [23][24][25]. In our study, we found that adenoidectomy has a positive effect on pulmonary functions, and after surgery, there were significant improvements in three spirometric parameters:…”
Section: Discussionmentioning
confidence: 61%